Presencia de doble estro anual en una hembra de lobo mexicano (Canis lupus baileyi) en cautiverio - Soto, Ma. de la Asunción; Vázquez, Carmen; Ramos, Xochitl; Yáñez L., Ma. de Lourdes; Armella, Miguel A. (THERYA, 2013)
As in most of the wolf subspecies, sexual behavior in Mexican wolf is shown in late winter once a year. Reproductive cycle in female wolves includes seasonality and monoestrum, with a long anestrus period. Estrogens and progesterone are responsible for estrus appearance and presence of both seems to be necessary for the full stimulation of sexual behavior in female wolves. In previous studies we made quantification of fecal estrogens and progesterone to several couples of Mexican wolves in captivity, in all the cases peaks on both hormones are correlated with reproductive behavior and shown in winter. Lately, another couple hosted in Aragon Zoo, Mexico City, shown, on in an unexpected way, sexual behavior during August in addition to the normal one in February; then we performed a sexual hormones analysis since this last periods in fecal samples. Results show a significant rise on female sexual steroid hormones concentrations in both, winter and summer. Female was checked for clinical and physical disorders, finding no evidence of pathologies. Pedigree was reviewed looking for possible hybridization, but only a pure wolf lineage was found, environmental factors were also studied providing no evidence that could explain such hormones concentrations. This is first report in summer of estrus behavior in Mexican wolf. Key words: anestrus, estradiol, monoestrum, progesterone, sexual behavior, testosterone.